Effect of replacing saw dust litter with dry Neem leaves for improving litter quality, immunity and foot pad condition of broiler birds - YADAV, R K; SINGH, N; SHARMA, S; GUJAR, G; CHANDRA, V; FOZDAR, A (The Indian Journal of Animal Sciences, 2026)
This experiment was an attempt to study the impact of replacing saw dust with dry neem leaves in litter for improving litter quality, immunity, and foot pad condition of broiler birds. The experiment was carried out in the institutional poultry farm during June 2024. Eighty White Leghorn broiler chicks (Cobb strain) were randomly divided into treatment and control group (40 in each) with each group having four replications having 10 birds each. The broiler chicks were reared in deep litter housing system made of saw dust (94%) along with dry Neem leaves (6%) with the control group reared on saw dust litter without dry neem leaves. The litter quality parameters viz., pH, moisture, water holding capacity (WHC), ammonia emission, nitrogen content and cake formation score; broiler immunity expressed as antibody titre against Newcastle disease and broiler welfare in terms of footpad condition were recorded weekly over the period of 6 weeks. The data was analysed using one way ANOVA followed by post hoc DMRT. Results revealed that the treatment group had a significantly higher antibody response against NDV (145.50 ± 3.50 vs. 14.00 ± 1.33), indicating enhanced immunological status. Welfare indicators such as foot pad condition (0.57 ± 0.28 vs. 1.29 ± 0.64) and reduced cake formation in litter (4.00 ± 0.00 vs. 5.00 ± 0.00) also reflected positive effects. Litter quality was substantially better in the treatment group, with lower moisture content (18.37 ± 0.17 vs. 26.77 ± 0.18), reduced pH (6.40 ± 0.04 vs. 6.95 ± 0.06), decreased ammonia emission (10.80 ± 0.46 vs. 23.05 ± 0.55), lower nitrogen content (15.89 ± 0.15 vs. 20.91 ± 0.11), and reduced parasitic load (11.67 ± 0.06 vs. 25.47 ± 0.06). Microbial load was also diminished, as reflected in the lower total viable count (6.64 ± 0.05 vs. 8.19 ± 0.06). Although water holding capacity did not differ significantly between groups, the overall findings demonstrate that the treatment group achieved superior immune response, improved welfare, and enhanced litter quality, underscoring its effectiveness in broiler management.